STUDI TINGKAT KEPEDULIAN MASYARAKAT SEKITAR HUTAN TERHADAP HUTAN LINDUNG GUNUNG PEMANCING - GUNUNG AMBAWANG KABUPATEN KUBU RAYA - Saputra, Dirga Kharies; Zainal, Sofyan; Riyono, Joko Nugroho (JURNAL HUTAN LESTARI, 2015)
Protected Forest of Mount Pemancing – Mount Ambawang in the area of Sungai Deras Village and Sungai Bemban Village are one of sources of local community life. The purpose of this study is to investigate the level of public awareness around the forest and the factors that have a relationship with the level of public awareness toward Protected Forest of Mount Pemancing - Mount Ambawang. This study was conducted in August 2015. The method used in this research is descriptive survey method by interview technique and questionnaire. Communities that were being sample in this study were determined by purposive sampling, the number of respondents in this study were 90. The results showed that 44 (48.88%) of the communities around forest in Sungai Deras Village and Sungai Bemban Village have a high level of concern for Protected Forest of Mount Pemancing - Mount Ambawang, 24 (26.66%) is moderate, and 22 (24.44%) is low. The high public awareness around forest toward Protected Forest of Mount Pemancing - Mount Ambawang in Sungai Deras Village and Sungai Bemban Village because some people have realized the importance of the role of Protected Forest of Mount Pemancing - Mount Ambawang for their lives. Keywords: Protected Forest, Awareness Level, Communities around Forest